Rib Fracture Management A Practical Manual (Springer International Publishing, 2018)
This text fills the educational gap for those trauma, orthopedic, and thoracic surgeons interested in learning the cutting edge evidence-based approaches to treatment of rib fractures. Although there has been ever increasing levels of interest and experience nationally there are many questions which remain. This text will provides not only the theoretical background for improving outcomes in those with rib fractures but also serve as a practical guide to those interested in starting new programs. The text includes tips and tricks that can be used in the operating room, or at the bedside to improve patient care. Therefore, the focus will be on a comprehensive review but also including tips and tricks from the most experienced surgeons around the country who are performing internal fixation for rib fractures. Rib Fracture Management .